2008
DOI: 10.2310/6670.2008.00007
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Thrombosis in Mice with Factor V Leiden Mutation

Abstract: The factor V Leiden (FVL) mutation has been demonstrated to be associated with the development of venous thrombosis in humans. Whether such a propensity also exists in the arterial circulation remains controversial. In an effort to minimize the variability that clouds the clinical study of arterial thrombosis, we studied FVL-associated arterial thrombosis in an experimental model of homozygous, heterozygous, and wild-type mice. Heterozygous FVL mice were crossbred to C57BL/6J mice over several generations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In animal studies, Sampram et al 11 found that the carotid arteries occluded within 60 minutes of injury in 97.3% of mice with Factor V Leiden mutation, homozygous occluding faster than heterozygous. Cooley et al 12 also demonstrated a higher propensity for arterial occlusion in homozygotes than in wild mice.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, Sampram et al 11 found that the carotid arteries occluded within 60 minutes of injury in 97.3% of mice with Factor V Leiden mutation, homozygous occluding faster than heterozygous. Cooley et al 12 also demonstrated a higher propensity for arterial occlusion in homozygotes than in wild mice.…”
Section: Discussionmentioning
confidence: 99%